2022
DOI: 10.1177/09763996221105143
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia Sustainable Tourism Resilience in the COVID-19 Pandemic Era: Case Study of Five Indonesian Super- priority Destinations

Abstract: This study was conducted to know Indonesia sustainable tourism resilience in the COVID-19 era. The research was done through a qualitative approach then analyzed based on the sentiment analysis and tourism resilience theory. The data used on this study are review data related to five super-priority tourism destinations in Indonesia, which are Borobudur Temple, Lake Toba, Labuan Bajo, Mandalika and Likupang since January 2020 to March 2021 from TripAdvisor. The result of this study shows that Indonesia sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Secondly, it helps enforce health regulations in the new normal age, encompassing measures such as restricting tourist numbers. A study conducted by Wibowo, JM., and Hariadi, S. [47] in Indonesia revealed that sentiment analysis outcomes about technological innovation had a notably elevated favorable attitude. This suggests that a of tourism destinations in Indonesia have commenced the process of incorporating technology into their operations.…”
Section: Table 2 Distribution Of Authorsmentioning
confidence: 99%
“…Secondly, it helps enforce health regulations in the new normal age, encompassing measures such as restricting tourist numbers. A study conducted by Wibowo, JM., and Hariadi, S. [47] in Indonesia revealed that sentiment analysis outcomes about technological innovation had a notably elevated favorable attitude. This suggests that a of tourism destinations in Indonesia have commenced the process of incorporating technology into their operations.…”
Section: Table 2 Distribution Of Authorsmentioning
confidence: 99%
“…The government has committed to investing in infrastructure, such as roads, bridges, and airports, to improve access to the region. In addition, plans are underway to develop a range of tourism facilities, including hotels, resorts, and cultural attractions (Pradjoko et al, 2021;Wibowo & Hariadi, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Now is the time for economic and social system recovery after the Covid 19 Pandemic (Daniel, 2020;De Leon et al, 2021;Kosack et al, 2021;Soekiman et al, 2021;Susilawati et al, 2020; J. M. Wibowo & Hariadi, 2022). Many restrictive policies from various countries have been eliminated or relaxed.…”
Section: Introductionmentioning
confidence: 99%